Pemanfaatan Maggot dan Pupuk Cangkang Telur di Cibuntu: dari Sampah Menjadi Manfaat - Abdul Aziz, Ridwan; Diva; Septiarosa, Putri; Maulana, Ilham; Laili, Khairunisa; Utami, Indri; Sindi Amelia, Rhika; Indria Melanie , Nazma; Putri Anantia , Sabilla; Bunga , Ailsa; Ahmad Gumelar , Zami; Nur hakim , Arif; Ananda , Tasya; Ote Fianury , Rinrin; Nainggolan , Mulya; Wildan, Fatwa; Febriana Yakhuhindah , Putri; Fauzan , Dhafin; Firgiawan , Wahyu; Johari , Eric; Rachmawati , Yuliani; Azhar Aldaira , Muh Dava; Ramadhan, Dimas; Ardiansyah , Ariel; Bianda , Azalia; Affandi Putra , Triana; Setiawan, Iwan (Jurnal Pengabdian Tri Bhakti, 2025)
The Community Service Program (KKN) in Cibuntu Sub-district, Bandung Kulon District, Bandung City, wascarried out as a form of student dedication to the community, with a focus on environmental issues, particularlyorganic waste management. Two flagship programs were introduced:“From Waste to Blessings: The Story ofCibuntu’s Maggots”and “Green Shell.” The first program was presented in the form of a documentary film thateducates the public about maggot cultivation as an eco-friendly solution for breaking down organic waste. The aim isto raise public awareness of alternative waste processing methods and to shape a positive image of Cibuntu as apioneer in environmental innovation. Meanwhile, Green Shell focuses on utilizing organic waste to produce compostfertilizer through planting activities, public outreach, and assistance in managing green spaces at the neighborhood(RW) level. Both programs involve active community participation as a form of empowerment and aim to encouragethe development of a sustainable, community-based waste management ecosystem. The outcomes of these activitiesshow increased public understanding and engagement in environmental issues, as well as the emergence ofopportunities to develop local innovations based on regional potential.Thus, this KKN initiative is expected to serve asa model for collaboration between academia and the community in achieving sustainable development at the sub-district level.